Expectations investing : - Rappaport, Alfred (Harvard Business School Press, 2001)
Expectations Investing offers a unique and powerful alternative for identifying value-price gaps. Rappaport and Mauboussin provide everything the reader needs to utilize the discounted cash flow model successfully. And they add an important twist: they suggest that rather than forecasting cash flows, investors should begin by estimating the expectations embedded in a company's stock price. An investor who has a fix on the market's expectations can then assess the likelihood of expectations revisions. To help investors anticipate such revisions, Rappaport and Mauboussin introduce an "expectations infrastructure" framework for tracing the process of value creation from the basic economic forces that shape a company's performance to the resulting impact on sales, costs, and investment. Investors who use Expectations Investing will have a fundamentally new way to evaluate all stocks, setting them on the path to success. Managers will be able to use the book to devise, adjust, and communicate their company's strategy in light of shareholder expectations.